PLAGUE THE HIDDEN OLD NEMESIS - Syed Nauman Raza et al (Baqai Journal of Health Sciences)
Plague is a disease of rodents carried to man by fleas and is non-existent in Pakistan. It represents a typical example of the evolution of human disease from an infection, originally confined to wild animals. Due to the closeness of Pakistan with India, the danger exists where it can become entrenched in the wild animals. It should be considered in the differential diagnosis in patients who lives in the endemic area or have exposure to animals known to harbor the vector. An attempt has been made in this review to understand the bionomics, clinical findings, diagnosis, epidemiology and prevention of the disease